PERAN PERGURUAN TINGGI DALAM SOSIALISASI UNDANG – UNDANG ITE NOMOR 19 TAHUN 2016 TENTANG CYBER CRIME-BULLYING DI DUKUH RANDUSARI, KARANGGENENG BOYOLALI - ABDUL CHAMID CHAIDAR; DWI KRISTIANI (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2021)
Social media, which is now being used more and more by all groups, has a positive and negative impact. Currently, cyberbullying cases are rife, namely bullying that occurs through cyber media, in this case, social media. Cyberbullying has a negative impact on victims, such as causing depression, to the worst, causing death by suicide. Cyberbullying is often a big problem both at national and global levels. There have been many cases, most of which are teenagers who commit suicide because they are cyberbully. Because of this, researchers are interested in further researching cyberbullying.